Phytochemical Profiling of Aquilaria malaccensis Lam. Essential Oils and their Antiproliferative Potential against HeLa Human Cervical Cancer Cells - Zaid, Atiqah; Alkatib, Huda Hisham; Sharulezam, Siti Nurhidayah; Yahaya, Noorfatimah; Lee, Tien Ping; Sreenivasan, Sasidharan; Wong, Yong Foo (Natural Products Journal, The, 2025)
BackgroundAquilaria malaccensis Lam. is one of the very few lign-aloes trees that can produce highly valuable resin-impregnated heartwood, commonly known as agarwood.AimThis study aimed to determine the chemical profile of A. malaccensis essential oil and describe its antiproliferative effects against the HeLa cervical cancer cell line.MethodThe essential oils hydro-distilled from agarwood were characterised using GC−MS with the aid of spectral deconvolution. The antiproliferative effects were evaluated via the MTT assay.ResultA total of 143 metabolites were tentatively identified in two different grades of essential oils, which accounted for 56.80% and 78.19% of the total ion counts, respectively. These metabolites were distributed over the chemical families of monoterpenes, sesquiterpenes, cyclic hydrocarbons, and others. The essential oils exhibited antiproliferative activities, with IC50 values of 79.42 and 128.77 µg/mL, respectively.ConclusionThe results have suggested the chemical differences in secondary compounds to be the main factor contributing to the decrease in cell viability. Further investigations are warranted to understand its mechanisms of action and its potential use in cervical cancer treatment.
Keywords: mass spectrometry